PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL INKUIRI TERBIMBING PADA MATERI GARIS SINGGUNG PERSEKUTUAN LINGKARAN KELAS VIII - Nurhayati Nurhayati; Kartini Kartini; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to produce mathematic learning device in the form of syllabus, lesson plan, and student worksheet using the guided inquiry learning model on the subject of tangent between two circle for VIII grade students. The study model used is 4-D that consist of define, design, develop, and desseminate. The research instrument used is validity device and practicality device. The validity device is a validation sheet to assess the feasibility of syllabus, lesson plans and student worksheet. The practicality device is in the form of observation sheet of learning process implementation and questionnaire of student response. Learning device developed are validated by five validators. The research trials were conducted in SMP Negeri 8 Pekanbaru which is tested in a small group and large group. Small group trial aims to assess the practicability based on student response questionnaire, while the large group to assess the practicability based on the observation sheet of learning process implementation and student response questionnaire. Based on the data analysis, it can be conclude that the average value for syllabus is 3.5 in very valid category which means that syllabus is feasible to be used; as well as the average value for lesson plan and student worksheet are 3.58 and 3.49. That are in very valid category which means that lesson plan and student worksheet are feasible to be tested. The student worksheet valued as very practical with mean score for small group and large group testing are 3.49 and 3.37. The lesson plan also valued as very practical with mean is 3.64. These categories mean that the lesson plan and student worksheet are feasible to used in school.Key Words: Mathematics Learning Device, Guided Inqury, Development Research, 4-D Model